2020
DOI: 10.1038/s42003-020-01437-8
|View full text |Cite
|
Sign up to set email alerts
|

Human TRPC5 structures reveal interaction of a xanthine-based TRPC1/4/5 inhibitor with a conserved lipid binding site

Abstract: TRPC1/4/5 channels are non-specific cation channels implicated in a wide variety of diseases, and TRPC1/4/5 inhibitors have recently entered clinical trials. However, fundamental and translational studies require a better understanding of TRPC1/4/5 channel regulation by endogenous and exogenous factors. Although several potent and selective TRPC1/4/5 modulators have been reported, the paucity of mechanistic insights into their modes-of-action remains a barrier to the development of new chemical probes and drug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 60 publications
3
41
0
Order By: Relevance
“…It is reported that Pico145, an HC-070 analogue, is more potent against hTRPC4/5 than HC-070 ( Just et al, 2018 ), possibly due to the substitution of chloride with trifluoromethoxy group on the chlorophenoxy ring of HC-070 ( Figure 6—figure supplement 2G–H ). Indeed, recent structure study showed that Pico145 binds to hTRPC5 channel using a similar pose as HC-070, except the chlorophenoxy ring with a trifluoromethoxy group on it inserts into a cavity surrounded by L521, Y524, F576, and V610 of hTRPC5 ( Figure 1—figure supplement 7J ; Wright et al, 2020 ). Another HC-070 analogue, AM237, is a TRPC5 activator with EC 50 around 15–20 nM ( Minard et al, 2019 ), and AM237 activates homomeric hTRPC5 channel instead of the heterotetrameric TRPC1: C5 channel ( Minard et al, 2019 ), suggesting that AM237 also binds at IBP-B which is at the interface between adjacent subunits.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It is reported that Pico145, an HC-070 analogue, is more potent against hTRPC4/5 than HC-070 ( Just et al, 2018 ), possibly due to the substitution of chloride with trifluoromethoxy group on the chlorophenoxy ring of HC-070 ( Figure 6—figure supplement 2G–H ). Indeed, recent structure study showed that Pico145 binds to hTRPC5 channel using a similar pose as HC-070, except the chlorophenoxy ring with a trifluoromethoxy group on it inserts into a cavity surrounded by L521, Y524, F576, and V610 of hTRPC5 ( Figure 1—figure supplement 7J ; Wright et al, 2020 ). Another HC-070 analogue, AM237, is a TRPC5 activator with EC 50 around 15–20 nM ( Minard et al, 2019 ), and AM237 activates homomeric hTRPC5 channel instead of the heterotetrameric TRPC1: C5 channel ( Minard et al, 2019 ), suggesting that AM237 also binds at IBP-B which is at the interface between adjacent subunits.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, two distinct inhibitor-binding sites were identified in the hTRPC6 channel ( Bai et al, 2020 ; Tang et al, 2018 ). During the editorial process of this work, inhibitor binding sites were also identified in TRPC4 ( Vinayagam et al, 2020 ) and TRPC5 ( Wright et al, 2020 ). Together with the sites identified in this study, we classify them into three groups, namely inhibitor-binding pocket (IBP) A-C ( Figure 6 , Figure 6—figure supplement 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pico145 (C31, HC-608) is a xanthine derivative that potently inhibits TRPC1/4/5 channels with IC 50 of 1.3 nM (TRPC5:C5), 0.349 nM (TRPC4:C4), 0.199 nM (TRPC5:C1, heteromers), and 0.033 nM (TRPC4:C1, heteromers) (Rubaiy et al 2017b ). Pico145 can directly, reversibly, and competitively inhibits the AM237-mediated TRPC5:C5 channel activation (Rubaiy et al 2017a ; Minard et al 2019 ; Wright et al 2020 ). The potency of Pico145 depends on the concentration of the (−)-englerin A (Rubaiy et al 2017b ).…”
Section: Trpcs Antagonistsmentioning
confidence: 99%